The influences of teachers regulative discourse, specifically teachers expectations of learner achievement on teachers' pedagogic practice in teaching Grade 6 Natural Science in the Western Cape : two case studies - Carder, Rebecca Jean (School of Education, 2015)
This study examines how two Grade 6 Natural Science teachers in two low SES schools in the Western Cape teach Natural Science, and what relation this has to the regulative discourse that informs their teaching. Data texts were derived from interviews and lesson observations. The study draws on research relating to teacher expectations and redescribes this in terms of Bernstein’s concept of the regulative discourse. The study concludes that the teachers’ regulative discourses and instructional discourses are not wholly developed individually; instead, these discourses, and specifically teachers’ expectations of learners are strongly influenced and developed by interactions between curriculum demands and the local school culture.